Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Step-by-step explanation:
y-intercept c = 3
y = mx + c
At (6,0)
0 = 6m + 3
m = - 1/2
y = f(x) = 3 - (1/2)x
(1/2)x = 3 - y
x = 2(3-y)
f^-1(x) = 2(3 - x)
f^-1(0) = 2(3 - 0)
= 0
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.